Otis & Sydney and the Best Birthday Ever - Numeroff, Laura Joffe; Andreasen, Dan (New York : Abrams Books for Young Readers, 2010)
Otis plans a surprise party for his best friend, Sydney, and although he has put the wrong date on the invitations and no one else comes, the two still have a wonderful time together.
Keywords: Friendship -- Fiction; Birthdays -- Fiction; Parties -- Fiction; Bears -- Fiction